Bilateral Leydig cell tumor of the testis: a case report - Sönmez, Nurettin; Ton, Özlem; ArIsan, Serdar; KIlInç, Fatih; Eken, Kamile; Güney, Soner (Contemporary Oncology/Współczesna Onkologia, 2012)
Leydig cell tumors are rare testicular tumors of the male gonadal interstitium. Although uncommon, Leydig cell testicular neoplasms are the most common sex cord-stromal tumors and comprise 1–3% of all testicular neoplasms. This tumor is always benign in children and approximately 90% are benign in adults. In most cases, patients present with an incidental finding of a testicular mass on scrotal ultrasonography during evaluation of hydroceles or varicoceles or during diagnostic workup for infertility. Leydig cell tumors have been primarily managed with radical inguinal orchiectomy. However, conservative management with testis-sparing surgery in younger adults and children were reported in the literature. Here we report a case of bilateral Leydig cell tumor of the testis treated with radical orchiectomy who presented with the complaint of infertilityand no disease recurrence in followup for 9 months. The patient is currently disease-free and under androgen supplemantation for androgen insufficiency. We recommend complete exam and diagnostic workup in patients with infertility and azoospermia.